Clarifying the atrioventricular junctional anatomy in the setting of double outlet right atrium - Saurabh Kumar Gupta (Annals of Pediatric Cardiology, 2015)
Double outlet atrium is a rare cardiac anomaly wherein one of the atriums, most frequently the right atrium, opens into both the ventricles. Although seen more commonly in the setting of atrioventricular septal defect, this arrangement can also be found when one of the atrioventricular connections is atretic due to absence of the atrioventricular connection and the other atrioventricular valve straddles the muscular ventricular septum. It is the specific anatomy and connections of the atrioventricular junction that clarifies the situation and distinguishes between these two types of double outlet atrium. In this report, we present a case of double outlet right atrium co-existing with the absence of left atrioventricular connection. We then discuss the morphologic aspects of this interesting anomaly.